STANDARDIZATION OF DOSES OF PHOSPHORUS AND POTASIUM ON GROWTH AND FRUIT QUALITY OF YOUNG KINNOW (CITRUS RETICULATE BLANCO) - Amina Alvi; M. Z. Rashid; M. Asim; S. Shahzad; S. Muqeet (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences, 2021)
Plants require a balanced nutrition program formulated to provide specific needs for maintenance and for expected production performance. Hence this experiment was conducted to evaluate the optimum level of phosphorus and potassium for growth and productivity of young Kinnow (Citrus reticulata Blanco) plants. The experiment was designed under Randomized Complete Block Design (RCBD) comprised with seven treatments and replicated thrice. The treatments included, T1= 200 g P2O5 + 200 g K2O, T2= 150 g P2O5 + 200 g K2O, T3= 250 g P2O5 + 200 g K2O, T4= 300 g P2O5 + 200 g K2O, T5= 250 g P2O5 + 150 g K2O, T6= 200 g P2O5 + 250 g K2O and T7= 200 g P2O5 + 300 g K2O. Maximum plant height (3.12 m) and Juice (43.48%) was observed in T5= 250 g P2O5 + 150 g K2O. The highest number of flush (33.08), number of leaves (101.25 m2), length of flush (13.75 cm), Seed weight (1.33 g), Aborted seeds/fruit (8), mature seed fruit (5.48) were noted in T7. Leaf area index and peel thickness were significantly increased in T6= (200 g P2O5 + 250 g K2O) with values 1.91 cm3 and 4.30 mm respectively. So, it is concluded that T5= 250 g P2O5 + 150 g K2O and T7= 200 g P2O5 + 300 g K2O is the best treatments for the growth and better yield of young Kinnow plants.